2007
DOI: 10.1111/j.1360-0443.2007.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol dependence with comorbid drug dependence: genetic and phenotypic associations suggest a more severe form of the disorder with stronger genetic contribution to risk*

Abstract: These analyses provide specific genetic evidence suggesting that alcohol dependence with comorbid drug dependence represents a particularly severe form of the disorder, with higher genetic contribution to vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 46 publications
5
70
1
2
Order By: Relevance
“…A history of psychiatric disorders such as internalizing (mood and anxiety disorders-e.g., Burns and Teesson, 2002) and externalizing (drug use disorders, antisocial personality disorder; Dick et al, 2007), mania (Goodwin and Jamison, 2007), and posttraumatic stress disorder (Bremner et al, 1996) are associated with a chronic course of problem drinking among individuals with AUD (Finney and Moos, 1992;Sher et al, 2005;Zucker et al, 2006). Furthermore, prior twin research, including prospective studies (e.g., Edwards et al, 2011;Hicks et al, 2007), has found that genetic effects contribute to signifi cant variation in these disorders as well as covariation with AUDs (Krueger et al, 2002;Pickens et al, 1995;Todorov et al, 2006).…”
Section: Untangling Genetic and Environmental Infl Uences In The Predmentioning
confidence: 99%
“…A history of psychiatric disorders such as internalizing (mood and anxiety disorders-e.g., Burns and Teesson, 2002) and externalizing (drug use disorders, antisocial personality disorder; Dick et al, 2007), mania (Goodwin and Jamison, 2007), and posttraumatic stress disorder (Bremner et al, 1996) are associated with a chronic course of problem drinking among individuals with AUD (Finney and Moos, 1992;Sher et al, 2005;Zucker et al, 2006). Furthermore, prior twin research, including prospective studies (e.g., Edwards et al, 2011;Hicks et al, 2007), has found that genetic effects contribute to signifi cant variation in these disorders as well as covariation with AUDs (Krueger et al, 2002;Pickens et al, 1995;Todorov et al, 2006).…”
Section: Untangling Genetic and Environmental Infl Uences In The Predmentioning
confidence: 99%
“…Further support for a role for the cholinergic system in addiction come from studies looking at the association of gene sequence variation, with changes in the M5 receptor gene sequence being associated with increased smoking and increased risk of developing cannabis dependence [88]. Variations in the M2 gene sequence were associated with a combination of alcohol and comorbid drug dependence, but not alcohol dependence alone [89]. More recently, variations in the M2 receptor gene sequence have been associated with an increased risk of smoking/nicotine dependence [90].…”
Section: Muscarinic Receptors and Substance Abusementioning
confidence: 99%
“…Genes for both muscarinic and nicotinic cholinergic receptors play a significant role in concurrent alcohol and opioid dependence (22,23) between subjects with heroin addiction, alcohol addiction, or controls. This study also did not find an association between HTR2A A-1438G polymorphism and alcohol or opioid addiction (25).…”
Section: Cholinergicmentioning
confidence: 99%